2018
DOI: 10.1002/admt.201870022
|View full text |Cite
|
Sign up to set email alerts
|

Transistors: Biaxially Stretchable Fully Elastic Transistors Based on Rubbery Semiconductor Nanocomposites (Adv. Mater. Technol. 6/2018)

Abstract: In article number 1800043, Cunjiang Yu and co-workers develope fully elastic stretchable transistors. The transistors are fabricated based on a solution process and can be stretched bi-axially with 125% areal strain while retaining stable operation and device characteristics. This Frontispiece illustrates the rubbery semiconductor from polythiophene nanofibrils in a percolated fashion and the transistor array in a deformed format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Although this blending technique to prepare rubbery semiconductors has been known, it has more recently invited attention due to the rising interest in stretchable electronics. Among many insulating elastomers, PDMS is one of the widely used materials to fabricate rubbery semiconductor composites through this blending approach . Song et al reported a blend containing prepared P3HT NWs (P3HT‐NWs) in PDMS for a stretchable semiconductor .…”
Section: Rubbery Semiconductorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although this blending technique to prepare rubbery semiconductors has been known, it has more recently invited attention due to the rising interest in stretchable electronics. Among many insulating elastomers, PDMS is one of the widely used materials to fabricate rubbery semiconductor composites through this blending approach . Song et al reported a blend containing prepared P3HT NWs (P3HT‐NWs) in PDMS for a stretchable semiconductor .…”
Section: Rubbery Semiconductorsmentioning
confidence: 99%
“…Similarly, Kim et al prepared P3HT nanofibrils (P3HT‐NFs) by heating (60 °C) and cooling (−20 °C) for self‐assembled, highly crystalline P3HT‐NFs to blend with PDMS for fully rubbery electronics and sensors (Figure b) . SEBS has also been recently used as an elastomer for stretchable electronics because of its superior mechanical softness, as demonstrated by Shin et al's use of P3HT and SEBS as a rubbery semiconductor composite (Figure c) . They used the blend after cooling (−15 °C) and warming (25 °C) before spin casting to form a high quality P3HT‐NF film.…”
Section: Rubbery Semiconductorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thin, soft skin‐integrated electronics have attracted great attentions due to their advantages such as flexible, lightweight, and mechanical compatible with human body, thus offer unique capabilities in detecting vital information and continuous monitoring human health . Recent advances in materials development, electronics miniaturization, mechanics optimization, and system‐level integration build up the foundations for flexible and stretchable electronics which are able to be integrated together with skin. Considering power supply for this new kind of soft electronics, conversion of mechanical energy from human body activities and motions to electricity is a considerable route .…”
Section: Introductionmentioning
confidence: 99%